2022
DOI: 10.1101/2022.11.08.22282079
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Every Mind Matters campaign in England: changes in mental health literacy over 30 months and associations between campaign awareness and outcomes

Abstract: Background The Every Mind Matters campaign and web resource launched in October 2019 by Public Health England aimed to equip adults to take action to improve their mental wellbeing by providing NHS-assured resources. The aim of this study is to investigate the effects on population level mental health literacy of Every Mind Matters over 30 months following campaign launch. Methods To observe changes in mental health literacy over time, we conducted regression analyses on a nationally representative, repeated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Web analytics showed that, between October 2019 and Febru ary 2021, the Mind Plan for supporting one's mental health was completed over three million times, against a target of one million for the first year. However, in contrast to this high level of usageand despite small improvements from September 2019 to March 2020 in knowledge of management for stress, depression and anx iety, mental health vigilance, sleep literacy, psychological well being and self efficacy -by March 2022 there was a deterioration in all outcomes compared to the September 2019 baseline, except for sleep literacy which was unchanged 6 .…”
Section: Challenges In Improving Mental Health Literacy At Population...mentioning
confidence: 87%
“…Web analytics showed that, between October 2019 and Febru ary 2021, the Mind Plan for supporting one's mental health was completed over three million times, against a target of one million for the first year. However, in contrast to this high level of usageand despite small improvements from September 2019 to March 2020 in knowledge of management for stress, depression and anx iety, mental health vigilance, sleep literacy, psychological well being and self efficacy -by March 2022 there was a deterioration in all outcomes compared to the September 2019 baseline, except for sleep literacy which was unchanged 6 .…”
Section: Challenges In Improving Mental Health Literacy At Population...mentioning
confidence: 87%
“…1 Measurement: Development of three new measures of mental health literacy (recognition, action, vigilance) (11) suitable for the content of EMM and use in general population samples. 2 Change in outcomes over time and their relationship to EMM awareness or use: Quantitative analysis of data from repeated bespoke surveys of nationally representative samples before and since the launch of EMM using the above measures and others based on the Kutcher definition of mental health literacy (12). 3 Economic evaluation: Analysis of the Health Survey for England 2019 2 dataset to assess whether use/awareness of EMM moderates the relationships between wellbeing and helpseeking, and wellbeing and the costs of primary care use; and modelling using the repeated bespoke surveys to examine the cost-effectiveness of the campaign (improvements in health literacy and well-being).…”
Section: Introductionmentioning
confidence: 99%
“…Change in outcomes over time and their relationship to EMM awareness or use: Quantitative analysis of data from repeated bespoke surveys of nationally representative samples before and since the launch of EMM using the above measures and others based on the Kutcher definition of mental health literacy (12).…”
Section: Introductionmentioning
confidence: 99%